2021
DOI: 10.3758/s13428-020-01533-x
|View full text |Cite
|
Sign up to set email alerts
|

The Croatian psycholinguistic database: Estimates for 6000 nouns, verbs, adjectives and adverbs

Abstract: Psycholinguistic databases containing ratings of concreteness, imageability, age of acquisition, and subjective frequency are used in psycholinguistic and neurolinguistic studies which require words as stimuli. Linguistic characteristics (e.g. word length, corpus frequency) are frequently coded, but word class is seldom systematically treated, although there are indications of its significance for imageability and concreteness. This paper presents the Croatian Psycholinguistic Database (CPD; available at: 10.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 91 publications
2
9
0
1
Order By: Relevance
“…Similar claims can be found in many other citing works (Utama et al, 2020;van Noord et al, 2020;Hovy and Yang, 2021;Sayers et al, 2021;Peti-Stantić et al, 2021;Jang and Lukasiewicz, 2021). While Bender and Koller raise important points for discussion, these strong implications in citing works are misleading and potentially harmful.…”
Section: Strong Claims About Understandingsupporting
confidence: 64%
“…Similar claims can be found in many other citing works (Utama et al, 2020;van Noord et al, 2020;Hovy and Yang, 2021;Sayers et al, 2021;Peti-Stantić et al, 2021;Jang and Lukasiewicz, 2021). While Bender and Koller raise important points for discussion, these strong implications in citing works are misleading and potentially harmful.…”
Section: Strong Claims About Understandingsupporting
confidence: 64%
“…Valence effects can be modulated by word classes because different word classes have different emotional arousal and processing mechanisms for an individual (Kolbeneval and Alexandrov, 2016;Zhang, 2019a). Nouns, verbs, and adjectives are different in their concreteness, imageability, and semantic references, indicating different complexity in recognition and processing (Gleitman, 1990;Xia et al, 2016;Peti-Stantić et al, 2021). Some studies even found that different word classes were associated with different neurons, and thus had different stability, consistency and gradability (Waxman and Booth, 2001;Kolbeneval and Alexandrov, 2016).…”
Section: Research Backgroundmentioning
confidence: 99%
“…While it is generally suggested that valence play a crucial role in lexical processing, the bulk of the previous studies have been prominently featured by discrete emotional stimuli limited to emotional face pictures or sentences (Wieser et al, 2014;Diéguez-Risco et al, 2015;Fan et al, 2018;Li et al, 2020) or lexical decision tasks (Barriga-Paulino et al, 2022) under laboratory settings. In addition, nouns and adjectives are different in their concreteness and imageability (Peti-Stantić et al, 2021), semantic references (Xia et al, 2016), and processing mechanism (Zhu et al, 2011;Kolbeneval and Alexandrov, 2016;Zhang, 2019a), which could modulate an individual's lexical processing with different valences under different contexts. Emotional experiences are 'ingredients' in the creation of emotional perceptions (Glenberg et al, 2009;Lindquist, 2017;Zhang, 2019a,b), and evidence from controlled laboratory settings cannot gauge fully an individual's real emotional experiences and their effects on emotional words processing (Pavlenko, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Datasets including concreteness norms are now available for several languages. To name just a few recent ones, Montefinese et al (2014) for Italian, Guasch et al (2016) for Spanish, Soares et al (2018) for Portuguese, Yao et al (2017) for Chinese, Bonin et al (2018) for French, Peti-Stantić et al (2021) for Croatian. For English, Brysbaert et al (2014) is among the most widely used.…”
Section: Theoretical Backgroundmentioning
confidence: 99%